Transferring and extrapolating estimates of cost-effectiveness for water quality outcomes: Challenges and lessons from the Great Barrier Reef. (October 2021) - Star, Megan; Rolfe, John; Farr, Marina; Poggio, Mark
Abstract: In recent decades the declining health of the Great Barrier Reef has led to a number of government policies being implemented to reduce pollutant loads from the adjacent agricultural-based catchments. There is increasing use of cost-effectiveness measures to help prioritise between different programs and actions to reduce pollutants, given limited resources and the scale of the issues. However there are a small number of primary studies available, and the consistency of cost-effectiveness measures and their application is limited, particularly given the various uncertainties that underlie the measures. Unlike Europe and the United States of America water policy or benefit transfer approaches, there are no procedural guidance studies that must be followed in the context of the Great Barrier Reef catchments. In this study we review the use of cost effectiveness estimates for pollutant reduction into the Great Barrier Reef in the context of a benefit transfer framework, where estimates of costs from a particular case study are transferred to various scenarios within different catchments. The conclusions suggest a framework be developed for the Great Barrier Reef, which is consistent, transparent, and rigorous.